2012
DOI: 10.1016/j.cellsig.2012.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase A-mediated phosphorylation of RhoA on serine 188 triggers the rapid induction of a neuroendocrine-like phenotype in prostate cancer epithelial cells

Abstract: Whilst androgen ablation therapy is used to treat locally advanced or metastatic forms of prostate cancer, side-effects can include the emergence of an androgen-independent neuroendocrine cell population which is associated with poor prognosis. Here we have examined how cyclic AMP elevation regulates early events in the neuroendocrine differentiation process. We demonstrate that selective activation of protein kinase A is necessary and sufficient for cyclic AMP (cAMP) elevation to rapidly promote a neuroendocr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…The high levels of D1 expression induced by T3 are consistent with the positive feedback loop of the processes for NE differentiation (47). PKA directly induces the inactivation of an apoptotic factor (phosphorylation of BAD) (9), and it indirectly stimulates VEGF secretion (PI3K/AKT/hypoxia inducible factor-1α [HIF-1α]) (48) and neurite outgrowth by cytoskeleton rearrangements (inhibition of Ras homolog gene family A [RhoA]/Rho-associated protein kinase [ROCK]) (49). PKA also induces the phosphorylation of CREB and the expression of cell survival factors (Bcl-2), metalloproteases and NE peptides (NSE, CgA, SYP, neurotensin and so on) (8,9,36).…”
Section: Discussionsupporting
confidence: 53%
“…The high levels of D1 expression induced by T3 are consistent with the positive feedback loop of the processes for NE differentiation (47). PKA directly induces the inactivation of an apoptotic factor (phosphorylation of BAD) (9), and it indirectly stimulates VEGF secretion (PI3K/AKT/hypoxia inducible factor-1α [HIF-1α]) (48) and neurite outgrowth by cytoskeleton rearrangements (inhibition of Ras homolog gene family A [RhoA]/Rho-associated protein kinase [ROCK]) (49). PKA also induces the phosphorylation of CREB and the expression of cell survival factors (Bcl-2), metalloproteases and NE peptides (NSE, CgA, SYP, neurotensin and so on) (8,9,36).…”
Section: Discussionsupporting
confidence: 53%
“…Evidence indicates that RhoA itself is phosphorylated on Ser-188 by cGMP-dependent protein kinase (cGK), protein kinase A (PKA), and by Ste20-related kinase (SLK). [81][82][83] It has been shown that RhoA Ser-188 phosphorylation negatively regulates its function by promoting its association with RhoGDIs. 84 Thus, phosphorylation of all components has to be taken into account in order to describe the signaling network controlling RhoA.…”
Section: Discussionmentioning
confidence: 99%
“…S188 phosphorylation of RhoA suppresses RhoA signalling via RhoGDI (Rho GDP-dissociation inhibitor)-mediated relocalization of (GTP-bound) RhoA from the cellular membrane to the cytoplasm, thereby keeping RhoA away from its site of activity and preventing downstream signalling (Lang et al, 1996;Rolli-Derkinderen et al, 2005). Cyclic AMP (cAMP)-dependent protein kinase A (PKA) has been reported to phosphorylate RhoA at position S188 in several cell types (Dong et al, 1998;Ellerbroek et al, 2003;Jones & Palmer, 2012;Lang et al, 1996;Lapetina et al, 1989;Quilliam et al, 1991;Tkachenko et al, 2011). This is of particular interest as the US3 protein kinase homologues of alphaherpesviruses such as HSV-1 and VZV have been shown (i) to functionally overlap with cellular PKA with regard to cellular substrates and/or (ii) trigger activation of cellular PKA during infection (Benetti & Roizman, 2004;Benetti et al, 2003;Erazo & Kinchington, 2010;Munger & Roizman, 2001;Ogg et al, 2004).…”
mentioning
confidence: 99%